Lion of the Forest : James B. Finley, Frontier Reformer - Cole, Charles Chester (Book collections on Project MUSE., 2010)
James B. Finley -- circuit rider, missionary, prison reformer, church official -- transformed the Ohio River Valley in the nineteenth century. As a boy he witnessed frontier raids, and as a youth he was known as the ""New Market Devil"" In adulthood, he traveled the Ohio forests, converting thousands through his thunderous preaching-and he was not abovebringing hecklers under control with his fists. Finley criticized the federal government's Indian policy and his racist contemporaries, contributed to the temperance and prison reform movements, and played a key role in the 1844 division of the M.